Bullying victimization, physical inactivity and sedentary behavior among children and adolescents: a meta-analysis - Antonio García-Hermoso; Ignacio Hormazabal-Aguayo; Xavier Oriol-Granado; Omar Fernández-Vergara; Borja del Pozo Cruz (BMC, 2020)
Abstract Background Physical activity and sedentary behavior are related with psycho-social variables among youth, however its relationship with bullying victimization is unclear. The aim of the study was to clarify the associations between physical activity and sedentary behaviors with bullying victimization among children and adolescents. Methods Two independent authors searched in four databases. The studies were selected/included only if participants were children and/or adolescents and the relationship between physical activity and/or sedentary behavior with bullying victimization was reported. Random-effects meta-analyses were used. Results A total of 18 cross-sectional studies (including 386,740 children and adolescents, 51.8% females) were reviewed. Our study found that not meeting the physical activity guidelines (Odds Ratio [OR] = 1.14, 95% confidence interval [CI], 1.04 to 1.23) and excessive sedentary behavior (i.e., 2 h per day or more of screen time) (OR = 1.21, 95% CI, 1.14 to 1.28) were associated with 14 and 21% higher bullying victimization, respectively. Consistent associations were also found when we analyzed specific forms of bullying for sedentary behavior, including traditional and cyberbullying. Conclusions The present study establishes the first quantitative framework for understanding the influence of physical activity and sedentary behavior on bullying victimization, and lays the groundwork for future studies and interventions aimed to its promotion. Trial registration CRD42018099388 .